Host-pathogen dynamics under sterilizing pathogens and fecundity-longevity trade-off in hosts - Janoušková, Eva; Berec, Luděk (Journal of theoretical biology, 2018)
Infectious diseases are known to regulate population dynamics, an observation that underlies the use of pathogens as control agents of unwanted populations. Sterilizing rather than lethal pathogens are often suggested so as to avoid unnecessary suffering of the infected hosts. Until recently, models used to assess plausibility of pathogens as potential pest control agents have not included a possibility that reduced fecundity of the infected individuals may save their energy expenditure on reproduction and thus increase their longevity relative to the susceptible ones. Here, we develop a model of host-pathogen interaction that builds on this idea. We analyze the model for a variety of infection transmission functions, revealing that the indirect effect of sterilizing pathogens on mortality of the infected hosts, mediated by a fecundity-longevity trade-off, may cause hosts at endemic equilibria to attain densities higher than when there is no effect of pathogens on host mortality. On the other hand, an opposite outcome occurs when the fecundity-longevity trade-off is concave or when the degree of fecundity reduction by the pathogen is high enough. This points to a possibility that using sterilizing pathogens as agents of pest control may actually be less effective than previously thought, the more so since we also suggest that if sexual selection acts on the host species then the presence of sterilizing pathogens may even enhance host densities above the levels achieved without infection.
Keywords: Population Dynamics; Host-Pathogen Interactions; Pest Control; kontrola škůdců; interakce hostitele a patogenu; Mathematical model; Longevity; fertilita; sterilizace; zvířata; populační dynamika; Energy Metabolism; Population dynamics; energetický metabolismus; Fertility; teoretické modely; Infectious disease; dlouhověkost; Pest control; Animals; Models, Theoretical; Sterilization